Antarctic Climate Research Data, Part 1 Radiation Data at Syowa Station, Antarctica from February 1987 to January 1988 - ヤマノウチ, タカシ; YAMANOUCHI, Takashi (National Institute of Polar Research, 1989)
P(論文) departmental bulletin paper